The State of Governance Bangladesh 2016: regulation process performance - Rahman, Sultan Hafeez; Abdallah, Wahid; Enam, Ahmed Asif; Ferdous, Nahid; Rahman, Muhammad Ashikur; Rashid, Md. Harun-Or-; Razzaque, Farhana; Uddin, Mohammed Misbah; Zahan, Iffat; Zaman, Nabila; Zillur, Kaneta (BRAC Univeristy, 2018)
Includes bibliographical references (page 121 - 126).